Implementasi Program Kampus Mengajar Berbasis Numerasi di Kelas XI Geologi Pertambangan SMKN 4 Palangka Raya - Suprianto, Dede; Simarmata, Aditya D; Nainggolan, Angel M.; Atmaja, Hengki; Manalu, Joko C.H; Tinambunan, Lukas A.; Siringoringo, Michael R.S.; Rante, Neli (Universitas Negeri Gorontalo, 2026)
Implementation in improving numeracy was carried out in class XI of Mining Geology Department through the campus teaching program at SMKN 4 Palangka Raya. Activities carried out to improve literacy included an introduction to the 13th UPR Student Mining Competition (USMC), polygon framework mapping and data processing of theodolite measurement results, manual processing of theodolite data and making simple topographic maps as well as a discussion of blasting techniques. The implementation method was carried out interactively through a participatory approach and direct mentoring such as class discussions, questions and answers and direct practice so that students as the target of the activity could be actively involved in the learning process. From this activity, it was shown that students could gain insight and knowledge related to numeracy in the field of mining geology so that students could understand and make topographic maps from the results of calculations and manual processing of theodolite data.